Imagineering Cultural Vienna : On the Semiotic Regulation of Vienna's Culture-led Urban Transformation - Suitner, Johannes (Urban Studies, 2015)
Media and public discourses often consider Vienna as a "cultural city". This study of Vienna's recent planning practice and discourses shows how this perception is skilfully shaped by political constructions of cultural imaginaries in and of the city. The book unveils how simplistic cognitive interpretations of culture not only define an unquestioned, reductionist idea of the city's cultural character - it also explains how they influence the recent urban development practice in one of Europe's globalizing cities.